Hubungan Perilaku Caring Perawat Terhadap Kepuasan Pasien Di Poli Rawat Jalan Rumah Sakit Binakasih Pekanbaru - Senofia, Elta; Ayudytha, Awaliyah Ulfah; Ardeni, Ardeni (JURNAL PENDIDIKAN KESEHATAN, 2025)
Patient satisfaction is considered to have been achieved if the patient's needs, desires and expectations can be met. In addition, patient satisfaction can be achieved if the performance of the health services they receive is the same or exceeds their expectations. Patient dissatisfaction with health services is influenced by nurses' caring behavior. The aim of this research is to determine the relationship between nurses' caring behavior and patient satisfaction levels at Bina Kasih Hospital Pekanbaru. This research is a quantitative research with a cross sectional design. This research was conducted in October 2023. The population in this study was all patients at the Outpatient Clinic of Binakasih Hospital Pekanbaru, namely 110 people with a sample of 86 people. The sampling technique uses simple random sampling. The measuring tool in this research uses a questionnaire. Data analysis in this study used univariate and bivariate analysis with the chi square test. The research results showed that 54.3% of nurses said they were good at caring behavior. There was a relationship between caring behavior and 60.8% were satisfied with the service. There is a relationship between nurses' caring behavior and patient satisfaction levels at Bina Kasih Hospital Pekanbaru with a p value of 0.003. It is hoped that Adar hospitals can improve the competence of their human resources, especially in the field of nursing, by encouraging them to attend seminars in the field 3of the nursing profession as stated in the hospital planning at the point of increasing employee or human resource competency and also encouraging and planning improvements and improving service supporting facilities.